EVALUATION OF NOOTROPIC ACTIVITY OF ACHYRANTHES ASPERA LEAVES EXTRACT IN WISTAR RATS - Bhargavan, Divya; Kumari, Suchetha; B, Deepa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to evaluate the nootropic activity of hydroalcoholic extract of Achyranthes aspera leaves using elevated plus maze and radial arm maze. Methods: Adult Wistar rats were allotted to three groups; Group 1 served as control, Groups 2 and 3 received 200 mg/kg and 400 mg/kg of AA extract, respectively, orally for 2 weeks after which the extent of improvement of memory was assessed. Results: AA showed nootropic activity in both elevated plus maze and radial arm maze. 200 mg/kg of AA extract showed better improvement in learning and memory compared to 400 mg/kg. Conclusions: These results indicate that AA leaves extract clearly exhibited the improvement in learning and memory.